The state they're in : an agenda for international action on poverty in Africa - Lockwood, Matthew (Warwickshire, U.K. : ITDG Pub., 2005)
"Matthew Lockwood draws on a substantial body of research to argue that much thinking on Africa - from both official donors and from international NGOs alike - is flawed, because that thinking either does not recognize or does not draw out the implications of the central role of politics and the state in Africa's development problems." "The analysis leads to a different policy agenda for aid, trade, debt and corruption, and also a different campaigning agenda for NGOs: agendas that have a focus on support for the emergence of a new kind of politics in Africa."--BOOK JACKET.
Includes bibliographical references (p. [156]-172) and index.
Keywords: Poverty -- Africa